A systematic review of the factors associated with regret post-cancer treatment. Issue 1 (3rd January 2022) - Szproch, Aleksandra Karolina; Maguire, Rebecca
Abstract: Problem identification: Expanding on previous work in specific cancer populations, this review aimed to explore factors associated with decisional regret following treatment for a range of cancer types. Literature search: A systematic search of four databases identified 1747 studies, using search terms relating to cancer survivors and decisional regret. Following quality appraisal, correlates of regret were abstracted and analyzed using narrative synthesis. Data evaluation/synthesis: Seventy-two studies met the inclusion criteria. Factors associated with treatment regret were categorized as being either modifiable or less modifiable. Regret was associated with various sociodemographic factors, physical health, treatment type, an unsatisfactory decision-making process, poorer mental health and lack of social support. Conclusion: Results highlight the complex nature of regret and illustrate how this can be experienced following a range of cancer treatments. As regret can be an obstacle to full-recovery from cancer, this review suggests some ways in which the emergence of regret may be mitigated.